Into the unknown : the X-1 story - Rotundo, Louis C. (Washington, D.C. : Smithsonian Institution Press, 1994)
History of the X-1 program from the origins of high-speed research in the 1930s to Chuck Yeager's flight through the sound barrier on October 14, 1947.
Includes bibliographical references and index.
Booklist.
Choice.
Reference and Research Book News.
Booklist, November 1996.
Choice, February 2009.
Keywords: Bell X-1 (Supersonic plane); High-speed aeronautics -- History; Supersonic planes -- Research -- United States -- History; Aeronautics -- History; Bell X-1 (Supersonic plane); Supersonic planes -- Research